2016
DOI: 10.1590/1980-5373-mr-2015-0100
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Zinc Tungstate (ZnWO4) Particles by Solvo-hydrothermal Technique and their Application as Support for Inulinase Immobilization

Abstract: ZnWO 4 particles were synthesized as a single-phase by a simple and easy solvo-hydrothermal technique using water-ethylene glycol mixture as solvent, without using surfactant. Physical properties of produced particles were analyzed by X-ray diffraction (XRD), infrared spectroscopy (FTIR), surface area (BET), particles size distribution and atomic force microscopy (AFM). This material was used as support for inulinase immobilization by physical adsorption and the influence of temperature (30 and 50 o C) was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…It was found that the kaolin particles are in the range of 0.72-120 μm, resulting in an average particle size of 23.45 μm (0.2345 mm). This particle size can explain the q ,exp i mesoporosity of material due to a variety of pore voids among the particles caused by its agglomeration 64 . Therefore, this mesoporous structure is interesting for adsorption purposes.…”
Section: Characterization Of Kaolinmentioning
confidence: 98%
“…It was found that the kaolin particles are in the range of 0.72-120 μm, resulting in an average particle size of 23.45 μm (0.2345 mm). This particle size can explain the q ,exp i mesoporosity of material due to a variety of pore voids among the particles caused by its agglomeration 64 . Therefore, this mesoporous structure is interesting for adsorption purposes.…”
Section: Characterization Of Kaolinmentioning
confidence: 98%
“…Concerning the oxyanions of Mo and W, the region of the appearance of Mo-O and W-O vibration bands, is practically the same for both metals [36]. The adsorption bands for Mo are reported in the region from 1000-700 cm −1 [37] and the stretching W-O between 880-820 cm −1 [38]. The CTS-Mo beads spectrum (red) shows a peak at 880 cm −1 of medium intensity and a shoulder near 840 cm −1 .…”
Section: Ftir Characterization For Beads Interactionsmentioning
confidence: 76%
“…The utilization of polyethylene glycol (PEG) during synthesis has proven to produce better nanoparticles. ZnWO 4 nanoparticles synthesized by Severo et al (2016) using PEG were assigned the monoclinic phase from the XRD data presented; this means the sample was single-phase. Paliki et al (2016) also synthesized ZnWO 4 nanoparticles for catalytic oxidation.…”
Section: Different Parameters Affecting the Nanoparticlesmentioning
confidence: 99%
“…This researcher also used PEG and obtained monoclinic wolframite nanoparticles; this process took place at room temperature. ZnWO 4 nanoparticles synthesized by Severo et al (2016) using (PEG) were assigned the monoclinic phase from the presented XRD data. It was also observed that the nanoparticles obtained had different accumulated pore voids on the surface of the particles due to the agglomeration of the particles.…”
Section: Different Parameters Affecting the Nanoparticlesmentioning
confidence: 99%